Monitoring performance, pituitary-adrenal hormones and mood profiles: how to diagnose non-functional over-reaching in male elite junior soccer players - Schmikli, S. L.; de Vries, W. R.; Brink, M. S.; Backx, F. J. G. (British Journal of Sports Medicine, 2012)
Objective To verify if in male elite junior soccer players a minimum 1-month performance decrease is accompanied by a mood profile and hormone levels typical of non-functional over-reaching (NFOR).Design A prospective case-control study using a monthly performance monitor with a standardised field test to detect the performance changes. Players with a performance decrease lasting at least 1 month were compared with control players without a performance decrease on mood scores and pre-exercise and postexercise levels of stress hormones.Setting Sporting field and sports medical laboratory.Participants Ninety-four young elite soccer players were monitored during the 2006-2008 seasons. Twenty-one players were invited to the laboratory, seven of whom showed a significant performance decrease.Main outcome measures Performance change over time, scores on the profile of mood states and premaximal and postmaximal exercise serum levels of adrenocorticotropic hormone (ACTH), growth hormone (GH) and cortisol.Results Players with a performance decrease showed psychological and hormonal changes typical of the non-functional state of over-reaching. Scores were higher on depression and anger, whereas the resting GH levels and ACTH levels after maximal exercise were reduced. ACTH and GH were capable of classifying all but one player correctly as either NFOR or control.Conclusions Performance-related criteria in field tests are capable of identifying players with worsened mood and adaptations of the endocrine system that fit the definition of NFOR. Performance, mood and hormone levels may therefore be considered as valid instruments to diagnose NFOR in young elite soccer players.